2016
DOI: 10.1080/02640414.2016.1235795
|View full text |Cite
|
Sign up to set email alerts
|

Increasing heat storage by wearing extra clothing during upper body exercise up-regulates heat shock protein 70 but does not modify the cytokine response

Abstract: Plasma heat shock protein 70 (HSP70) concentrations rise during heat stress, which can independently induce cytokine production. Upper body exercise normally results in modest body temperature elevations. The aim of this study was to investigate the impacts of additional clothing on the body temperature, cytokine and HSP70 responses during this exercise modality. Thirteen males performed 45-min constant-load arm cranking at 63% maximum aerobic power (62 ± 7%V̇O 2peak ) in either a nonpermeable whole-body suit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…52 Should chronic PH enhance IL-6R expression as is evident following EX training, 53 interventions capable of increasing both IL-6 and IL-6R, may provide a therapeutic basis for improving glycemic control. Moreover, it has recently been shown that acute PH elevates the anti-inflammatory cytokines IL-1ra and IL-10, 54 suggesting that chronic PH may benefit the inflammatory profile in a similar way to EX. However, long-term investigation of PH is required to corroborate this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…52 Should chronic PH enhance IL-6R expression as is evident following EX training, 53 interventions capable of increasing both IL-6 and IL-6R, may provide a therapeutic basis for improving glycemic control. Moreover, it has recently been shown that acute PH elevates the anti-inflammatory cytokines IL-1ra and IL-10, 54 suggesting that chronic PH may benefit the inflammatory profile in a similar way to EX. However, long-term investigation of PH is required to corroborate this hypothesis.…”
Section: Discussionmentioning
confidence: 99%